2013
DOI: 10.3109/10428194.2013.766732
|View full text |Cite
|
Sign up to set email alerts
|

Patients with polycythemia vera have worst impairment of quality of life among patients with newly diagnosed myeloproliferative neoplasms

Abstract: The quality of life (QoL) at the time of diagnosis of myeloproliferative neoplasm (MPN) has, to date, not been studied. One hundred and seventy-nine patients with MPN: 80 with essential thrombocythemia (ET), 73 with polycythemia vera (PV), 22 with primary myelofibrosis (PMF) and four with MPN undifferentiated, were included in this study. European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC-QLQC30) and the MPN-Symptom Assessment Form (MPN-SAF) were used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 28 publications
5
45
0
3
Order By: Relevance
“…MPN patients have been shown to have levels of fatigue far in excess of that of published norms (Brief fatigue index score of 4.9 vs. 2.2 out of 10, respectively) [4] but to date no other studies have compared the broad spectrum of MPN symptoms, evaluated by the MPN-SAF, with rates in the general population. Fatigue was the most commonly reported symptom among MPN-UK patients consistent with other reports in the literature [4,5,10,12,15,16]. Fatigue is a common symptom reported in clinical practice with 58% of patients in primary care reporting chronic fatigue [17].…”
Section: Discussionsupporting
confidence: 78%
“…MPN patients have been shown to have levels of fatigue far in excess of that of published norms (Brief fatigue index score of 4.9 vs. 2.2 out of 10, respectively) [4] but to date no other studies have compared the broad spectrum of MPN symptoms, evaluated by the MPN-SAF, with rates in the general population. Fatigue was the most commonly reported symptom among MPN-UK patients consistent with other reports in the literature [4,5,10,12,15,16]. Fatigue is a common symptom reported in clinical practice with 58% of patients in primary care reporting chronic fatigue [17].…”
Section: Discussionsupporting
confidence: 78%
“…2,3,5,6 We have previously reported that among patients with MF, the burden of constitutional symptoms is worse than that for other types of solid malignancies including breast cancer and is similar to that for patients with acute myeloid leukemia. 3 Of all MPN symptoms, fatigue stood apart as having the highest severity and prevalence for all MPN subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of MPN-related fatigue indicate that it occurs in 81% 2 to 95% 3 of patients with MPNs and is the predominant symptom regardless of MPN subtype. [2][3][4][5][6][7] This fatigue reduces both physical and social functioning and substantially impairs quality of life. 2 Fatigue is a particular challenge for clinicians and patients due to its multifactorial nature.…”
Section: Introductionmentioning
confidence: 99%
“…Other common aspects of the PV disease state, including blood hyperviscosity (Barbui et al , 2013) and splenomegaly (Mesa et al , 2007), may also play a role in the symptom profile of some patients. The overall PV‐related symptom burden, as measured by the MPN Symptom Assessment Form total symptom score (MPN‐SAF TSS), as well as the severity of individual symptoms, including fatigue (Emanuel et al , 2012; Abelsson et al , 2013) and itching (Siegel et al , 2013), have been associated with reduced quality of life in patients with PV.…”
mentioning
confidence: 99%